Meta-Analysis: Gestalt Counseling Contribution in Increasing Students’ Self-Confidence - Kurniasari, Filastri; Sanyata, Sigit; Nurjanah, Anisa Siti; Rojanah, Rojanah (Psikopedagogia, 2021)
This study aims to conduct a meta-analysis of the effectiveness of gestalt counseling in increasing students' self-confidence. The study meta-analyzed eight research results on the effectiveness of gestalt counseling in increasing students' self-confidence. Analysis was performed using a pre post contrasts meta-analysis. The results show the mean value of the weighted effect (M) of 3.484, meaning that the difference between the pre-test and post-test scores was 3.484. A positive value on M indicates that the post-test score is higher than the pre-test. The value of the mean effect size is a parameter that shows the effective contribution. Based on these data, it can be concluded that gestalt counseling is effective in increasing students' self-confidence. The results of this study are expected to conclude the effect of using gestalt counseling in schools to overcome students' self-confidence problems. In addition, the results of this study are useful for counselors in carrying out counseling, both individual and group counseling, to increase students' self-confidence.